Reducing maternal mortality in Peru. Where to begin? - Benavides, Bruno (2001)
Maternal mortality is one of the health indicators that more accurately expresses inequity and social exclusion. More than half a million maternal deaths occur annually worldwide. 99% happen in developing countries. Living in poverty limits women's access to economic resources, social and basic education. Thus, less able to make informed decisions on health and nutrition. Maternal mortality also expresses gender iniquity for decision-making, the basic rights and social services.